Cochrane Database of Systematic Reviews 2014
DOI: 10.1002/14651858.cd006681.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heparin for prevention of venous thromboembolism in patients with lower-leg immobilization

Abstract: Use of LMWH in outpatients significantly reduces VTE when immobilization of the lower leg is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 45 publications
2
64
1
Order By: Relevance
“…If required, LMWH would be used as the first-line treatment and would be used postsurgically until a level of mobility is restored sufficient to negate the risk. It is not universally agreed whether patients with immobilization of the lower legs require routine thromboprophylaxis and it is generally not recommended as a routine approach (Falck-Ytter et al, 2012), although the use of LMWH in these patients has been reported to be safe and effective where necessary (Ettema et al, 2008;Testroote et al, 2008). LMWH prophylaxis has also been found to be effective and safe in patients with short-term reductions in mobility (e.g., owing to leg fracture or arthroscopy); a meta-analysis of trials in such patients found a significant reduction in major VTE events on the order of 70%, at the expense of a nonsignificant 35% increase in the risk of major bleeding (Chapelle et al, 2014).…”
Section: Clinical Use As An Anticoagulant/ Antithromboticmentioning
confidence: 99%
“…If required, LMWH would be used as the first-line treatment and would be used postsurgically until a level of mobility is restored sufficient to negate the risk. It is not universally agreed whether patients with immobilization of the lower legs require routine thromboprophylaxis and it is generally not recommended as a routine approach (Falck-Ytter et al, 2012), although the use of LMWH in these patients has been reported to be safe and effective where necessary (Ettema et al, 2008;Testroote et al, 2008). LMWH prophylaxis has also been found to be effective and safe in patients with short-term reductions in mobility (e.g., owing to leg fracture or arthroscopy); a meta-analysis of trials in such patients found a significant reduction in major VTE events on the order of 70%, at the expense of a nonsignificant 35% increase in the risk of major bleeding (Chapelle et al, 2014).…”
Section: Clinical Use As An Anticoagulant/ Antithromboticmentioning
confidence: 99%
“…Without prophylaxis, immobilisation of the lower extremity is associated with an estimated VTE rate of 20% (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Low molecular weight heparin (LMWH) in lower limb immobilised patients, has in systematic reviews shown to give a small reduction of VTE, the incidence being 0-37% versus 4.3-40% without prophylaxis (5). However, a randomised controlled study on 105 patients immobilised in plaster cast after ATR surgery demonstrated no effect of LMWH (6).…”
Section: Introductionmentioning
confidence: 99%
“…In the German guidelines, thromboprophylaxis after casting is recommended; however, there is only little evidence in the literature. A recent meta-analysis observed symptomatic VTE in 2.5 % of patients without anticoagulant thromboprophylaxis, another trial found symptomatic VTE in 1 % of the patients [2,6]. These results are comparable with the results from the POT-CAST trial, with an incidence of symptomatic VTE of 1.8 % in patients not treated with LMWH [3].…”
Section: Thromboprophylaxis After Knee Arthroscopy and Lower Leg Castingmentioning
confidence: 54%